METHOD OF DETERMINATION OF GAZODYNAMIC PARAMETERS OF GAS TURBINE VEHICLES OF RESTRICTED CONTROLLABILITY AT TRANSFERRED MODES - Панін, В. В. (Proceedings of National Aviation University, 2020)
The method of determination of gas-dynamic parameters of gas turbine engines that are not measured in operation is given